Enhancement of Critical Current Density and Flux Pinning in Acetone and La2O3 Codoped MgB2 Tapes - 高召顺 马衍伟 王栋樑 张现平 淡路智 渡边和雄 (Chinese physics letters, 2010)
MgB2 tape samples with simultaneous additions of acetone and La2O3 were prepared by an in？situ processed powder-in-tube method. Compared to the pure and single doped tapes, both transport Jc and fluxing pinning are greatly improved by acetone and La2O3 codoping. Acetone supplies carbon into the MgB2 crystal lattice and increases the upper critical field, while the La2O3 reacts with B to form LaB6 nanoparticles as effective flux pining centers. The improvement of the superconducting properties in codoped tapes can be attributed to the combined effects of improvement in Hc2 and flux pinning.